MiR-29 Regulates de novo Lipogenesis in the Liver and Circulating Triglyceride Levels in a Sirt1-Dependent Manner - Hung, Yu-Han; Kanke, Matt; Kurtz, Catherine Lisa; Cubitt, Rebecca L.; Bunaciu, Rodica P.; Zhou, Liye; White, Phillip J.; Vickers, Kasey C.; Hussain, Mohammed Mahmood; Li, Xiaoling; Sethupathy, Praveen (Frontiers in Physiology, 2019)
MicroRNAs are known regulators of lipid homeostasis. We recently demonstrated that miR-29 regulates levels of circulating cholesterol and triglycerides, but the mechanisms remained unknown. In the present study, we demonstrated that systemic delivery of locked nucleic acid inhibitor of miR-29 (LNA29) through subcutaneous injection effectively suppresses hepatic expression of miR-29 and dampens de novo lipogenesis (DNL) in the liver of chow-fed mice. Next, we employed mice with liver-specific deletion of Sirtuin 1 (L-Sirt1 KO), a validated target of miR-29, and demonstrated that the LNA29-induced reduction of circulating triglycerides, but not cholesterol, is dependent on hepatic Sirt1. Moreover, lipidomics analysis revealed that LNA29 suppresses hepatic triglyceride levels in a liver-Sirt1 dependent manner. A comparative transcriptomic study of liver tissue from LNA29-treated wild-type/floxed and L-Sirt1 KO mice identified the top candidate lipogenic genes and hepatokines through which LNA29 may confer its effects on triglyceride levels. The transcriptomic analysis also showed that fatty acid oxidation genes respond differently to LNA29 depending on the presence of hepatic Sirt1. Overall, this study demonstrates the beneficial effects of LNA29 on DNL and circulating lipid levels. In addition, it provides mechanistic insight that decouples the effect of LNA29 on circulating triglycerides from that of circulating cholesterol.